Sustainability and Quality Management in Healthcare During COVID-19 - Fok, Lillian Y.; Morgan, Yun-Chen; Zee, Susan M. L. (Journal of Applied Business and Economics, 2022)
This study aims to examine the relationships between healthcare organizations’ sustainability performance and 1) green sustainability practices, 2) organizational culture, and 3) quality management practices. We proposed a conceptual model of the relationships and formulated three hypotheses. The findings showed that green initiatives and quality management practices affect healthcare organizations’ sustainability performance, specifically social and environmental performance. The findings did not support the contribution role of organizational culture on sustainability performance. This study provides important strategic guidance for healthcare professionals who work to balance the implementation of corporate green practices and the triple bottom line dimensions of sustainability performance. The results showed that positive sustainability outcomes can be achieved when healthcare organizations commit to environmental issues and strategically invest in cost-efficient and eco-friendly initiatives.